Proposed Strategies to Improve Access to Funding for MSME Using Soundness Assessment and AHP Method (Gelap Nyawang Case Study) - Atikah, Atikah; Nainggolan, Yunieta Anny (Granada El-Fath, 2024)
Access to funding remains a major challenge for Micro, Small, and Medium Enterprises (MSMEs) despite their vital role in economic growth. This study assesses the funding eligibility of MSMEs in Gelap Nyawang using the MSME Soundness Assessment, incorporating AHP Scoring, linear regression, and qualitative insights from financial institutions. Findings reveal that while most MSMEs have strong financial and non-financial scores, many fail to meet lender criteria, particularly Repayment Capacity (RPC) Installment To Disposable Income Ratio (IDIR) and bad governance. Linear regression results show that education is the only significant factor influencing MSME soundness, indicating a link between financial management skills and business sustainability. However, poor financial documentation and incomplete legal status remain major barriers to accessing credit. This study proposes strategies to improve MSME funding eligibility, including financial literacy programs, enhanced business documentation, and digital marketing adoption to scale up sales. The findings provide insights for financial institutions, The Greater Hub ITB, and policymakers in supporting financial inclusion and business growth.